Internalization of Islamic Values in Enhancing Tolerance Character Through Al-Qur'an and Hadith Learning at As-Syafi'iyah Islamic Elementary School, Pemuteran, Bali - Moh. Kosim; Moh. Ulum (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2026)
Religious and cultural diversity in multicultural societies requires students to develop strong tolerance character. This condition poses a challenge for Islamic schools in internalizing Islamic values, particularly within non-Muslim majority environments. This study aims to analyze the internalization of Islamic values in fostering students’ tolerance character through Al-Qur’an Hadith learning at Madrasah Ibtidaiyah As-Syafi’iyah Pemuteran, Bali. The study employed a qualitative approach with a case study design conducted from April 25 to May 10, 2026. The informants consisted of one principal, two teachers, and eight students selected through purposive sampling due to their direct involvement in the learning process. Data were collected through interviews, observations, and documentation and analyzed using the Miles, Huberman, and Saldaña interactive model. Data validity was ensured through source and technique triangulation. The findings indicate that the internalization of values was implemented through role modeling, habituation, and social interaction, which fostered respect for differences, harmonious coexistence, and strengthened students’ Islamic character and religious moderation.